Feedback in the evaluation of teaching activities and its influence on the research - Jacqueline Zamora Galindo; Luis Alberto Mass Sosa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
In times of COVID-19, the evaluation of teaching activities has been one of the pedagogical practices that have represented the greatest challenge for all those involved in carrying out academic actions. This article reflects on how the implementation of effective feedback during the evaluation process of teaching activities could influence the quality of the research. It is concluded that feedback is essential in this process, because it allows students to understand and integrate quality criteria into their behavior, which can be transferred to the context of other activities, such as research, with very positive influences on the results of the research.